Dermoscopic and histopathologic findings in diagnosing postpartum pemphigoid gestationis - Chandra, Rudi; Roesyanto-Mahadi, Irma Damayanti (UI Scholars Hub, 2024)
Background: Pemphigoid gestationis (PG) is an uncommon autoimmune vesiculobullous skin disorder associated with pregnancy, that occurs during mid-to-late pregnancy and immediate postpartum period. The diagnosis of PG is based on histopathology and direct immunofluorescence. Dermoscopy is a non-invasive diagnostic tool that provides a connection between macroscopic clinical dermatology and microscopic dermatopathology. Case Illustration: We reported a case of a 22-year-old primigravida woman with postpartum PG. This PG case was diagnosed clinically, dermoscopically, and histopathologically. Discussion: Since PG is thought to be a variation of the bullous pemphigoid (BP), the two resemble each other clinically and immunologically. The well-defined structures with brown-black dots in the central, yellowish translucent areas, follicular openings, peri-eccrine and perifollicular pigmentations, and a distorted pigment network were the dermoscopic findings of PG. To date, there is no literature about the dermoscopic features of PG. Conclusion: Dermoscopy is a simple non-invasive tool that can assist in making a rapid diagnosis, as well as in evaluating the prognosis, observing the response to treatment, and helping to determine the appropriate lesion and location for histopathological examination. We recommend that the dermoscopic features of PG in our case as a dermoscopic picture of PG.